Surface characteristics of porous coconut shell carbon impregnated with bimetallic catalysts - Ibrahim, Yakub; Khairul Anwar, Mohd Said; Norsuzailina, Mohamed Sutan; Yun Hin, Taufiq-Yap; Surahim, Mohamad (Universiti Malaysia Sarawak (UNIMAS), 2014)
Selective Catalytic Reduction catalyst (Cu-Mn/CSC) was derived from coconut shell carbon (CSC). The bimetallic catalysts, Copper and Manganese (Cu-Mn), were deposited onto CSC using wet impregnation technique while the calcination stage was performed under low temperature ambient air. The samples were then characterized using nitrogen adsorption-and-desorption, carbon dioxide temperature-programmed desorption, ammonia temperature-programmed desorption, hydrogen temperature-programmed reduction as well as scanning electron microscopy. The results showed that the synthesis process increased the external surface area and regulated the distribution of slit-shape pores on Cu-Mn/CSC. Besides, Cu-Mn was found to be reduced and the surface has more acidic groups compared to basic. These findings indicated the potential of using CSC as a precursor for NOx- Selective Catalytic Reduction catalyst.